Survey for ‘Candidatus Liberibacter’ and ‘Candidatus Phytoplasma’ in Citrus in Chile - Nicolas Quiroga; Camila Gamboa; Gabriela Medina; Nicoletta Contaldo; Fernando Torres; Assunta Bertaccini; Alan Zamorano; Nicola Fiore (Pathogens, 2021)
The considerable economic losses in citrus associated with ‘Candidatus Liberibacter’ and ‘Candidatus Phytoplasma’ presence have alerted all producing regions of the world. In Chile, none of these bacteria have been reported in citrus species. During the years 2017 and 2019, 258 samples presenting symptoms similar to those associated with the presence of these bacteria were examined. No detection of ‘Ca. Liberibacter’ associated with “huanglongbing” disease was obtained in the tested samples; therefore, this quarantine pest is maintained as absent in Chile. However, 14 plants resulted positive for phytoplasmas enclosed in subgroups 16SrV-A (12 plants) and 16SrXIII-F (2 plants). Although they have been found in other plant species, this is the first report of these phytoplasmas in citrus worldwide.